Analysis of Hemodialysis Duration as a Determining Factor of Quality of Life in Patients with Chronic Kidney Disease : A Cross-Sectional Study at Regional General Hospital, Bandung Regency, 2024 - Kusmiran, Eny; Tentry Fuji Purwanti; Hani Hanafiah (Universitas STRADA Indonesia, 2026)
Background: Chronic kidney disease (CKD) is a progressive global health problem, with hemodialysis serving as a vital life-sustaining therapy. The therapy duration potentially impacts patients’ quality of life due to physical, psychological, and social challenges. Purpose: This study aimed to investigate the relationship between the duration of hemodialysis and quality of life among CKD patients at Regional General Hospital, Bandung Regency, Indonesia. Methods: A cross-sectional correlational design was employed in May 2024 involving 80 CKD patients undergoing hemodialysis, recruited by accidental sampling. Duration of hemodialysis was obtained from medical records, while quality of life was measured using the validated Kidney Disease Quality of Life Short Form (KDQOL-SF36). Data were analyzed using descriptive statistics and the Chi-Square test, with significance set at α = 0.05. Results: The mean age of participants was 46.3 ± 8.9 years; 56.3% were male. Patients undergoing hemodialysis for more than 24 months constituted 45.0% of the sample. Quality of life was reported as good by 57.5% of respondents, moderate by 30.0%, and poor by 12.5%. A significant association was found between hemodialysis duration and quality of life (p < 0.001), with longer treatment durations correlating with better quality of life 86.1% of patients treated over 24 months reported good quality of life compared to 35.5% in those treated under 12 months. Conclusion: Longer duration of hemodialysis is significantly associated with improved quality of life among CKD patients, potentially reflecting enhanced coping and adaptation mechanisms. These findings highlight the necessity for holistic nursing care programs tailored to treatment duration to optimize patient outcomes.